Lebanon : the Politics of Frustration--The Failed Coup of 1961. - Beshara, Adel (History and society in the Islamic world., 2013)
Lebanon examines the ideological, political and social underpinnings of the attempted coup against General Chihab's government in Lebanon in 1961. The author analyzes the role of the Syrian Socialist Nationalist Party, the history of the army in Lebanon and it role in Lebanese politics and the impact of the coup on Lebanese political life. This book provides an extraordinary insight into the mechanisms of military coups in the Arab world and will be of interest to students and researchers of the history and politics of the Middle East.